Arctic Ocean warmings from the last glaciation to the present : implementing and assessing the reliability of planktic foraminiferal paleoreconstructions - Zamelczyk, Katarzyna Agnieszka (Universitetet i Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Zamelczyk, K., Rasmussen, T.L, Husum, K., Haflidason, H., de Vernal, A., Ravna, E.K., Hald, M. and Hillaire-Marcel, C.: 'Between two oceanic fronts : Paleoceanographic changes and calcium carbonate dissolution in the central Fram Strait during the last 20,000 years' (manuscript in revision for Quaternary Research). 2. Zamelczyk, K., Rasmussen, T.L., Husum, K. and Hald, M.: 'Marine calcium carbonate preservation vs. climate change over the last two millennia in the Fram Strait : implications for planktic foraminiferal paleostudies' (manuscript submitted to Marine Micropaleontology). 3. Zamelczyk, K., Husum, K., Rasmussen, T.L., Godtliebsen, F. and Hald, H.: 'Surface water conditions and calcium carbonate preservation in the Fram Strait during the late Weichselian 29,000-16,000 years BP', (manuscript to be submitted to Paleooceangraphy). 4. Spielhagen, R. F.,Werner, K., Aagaard-Sørensen, S., Zamelczyk, K., Kandiano,E., Budeus, G., Husum, K., Marchitto, T., and Hald, M.: 'Enhanced modern heat transfer to the Arctic by warm Atlantic Water', Science (2011), vol. 331 no. 6016:450-453. Available at http://dx.doi.org/10.1126/science.1197397 5. Werner, K., Spielhagen, R.F., Bauch, D., Hass, H.Ch., Kandiano, E. and Zamelczyk, K.: 'Atlantic Water advection to the eastern Fram Strait- Multiproxy evidence for late Holocene variability', Palaeogeography, Palaeoclimatology, Palaeoecology (2011), vol. 308 no. 3-4:264-276. Available at http://dx.doi.org/10.1016/j.palaeo.2011.05.030 The aim of the PhD study was to use planktic foraminifera to elucidate paleoceanographic variability and the preservation state of calcium carbonate in the eastern Fram Strait throughout the last 30,000 years. Sediment cores were studied using a multiproxy approach which included analyzing planktic and benthic foraminiferal fauna distribution patterns, measurements of stable isotopes (δ18O, δ13C), grain size analysis, IRD counts, and chemical analysis of bulk sediment. In addition, mean shell ...